Safety and health in informal sector: a case study occupational fatigue of porters at Legi Market, Surakarta - Hidayati, Ria Nuril; Surono, Agus; Jaladara, Vena (Universitas Gadjah Mada, 2021)
Purpose: Understanding the application of OSH Management System in the informal sector, especially the occupational fatigue management system for the porters working in Legi traditional market, Surakarta. Methods: The type of research was qualitative based research to describe the implementation of OHS Management System in the informal sector, especially the occupational fatigue management system for porters working in Legi traditional market, Surakarta. Results: OHS Management System’s promotive and preventive efforts, in this case, have not yet reached and involved the porters and have not focused on minimizing the risk of occupational fatigue. The weight of the load carried by porters exceeds the recommended weight threshold and their work posture had a risk of injury and occupational diseases. The occupational fatigue commonly experienced by the porters was such as muscle pain in the knees, lower back pain, and some even getting whole body pain. The problems in implementing OHS Management System at Legi traditional market were due to there was no lifting and transportation equipment available, Station of Occupational Health Effort (Pos UKK) administrators not been trained of implementing OHS in the workplace, and the lack of enthusiasm from the market management and the porters themselves in OHS. Conclusions: The implementation of the OHS Management System did not include efforts for minimizing occupational fatigue for the porters. The Pos UKK needs to involve the porter organization (SPTI) in the implementation of promotive and minimize efforts to manage occupational fatigue. It is necessary to form an OSH policy and committee with support and cooperation from all related parties such as the Trade Department (“Dinas Perdagangan”) which has the workplace area and the Health Department (“Dinas Kesehatan”) which supervise for OHS efforts in term of implementation of OHS Management System in the informal sector is highly expected.